Teachers’ Training Workshop on Assessing Student Learning Outcomes as Professional Development: A Case Study - Khalid Iqbal,Muhammad Idris, Fazal ur Rahman (PJE, 2023)
This study was conducted to analyze the role of in-service teachers training workshop conducted by PITE, based on assessing learning outcomes (SLOs) at grade 5th. In-service teachers’ trainings workshops play significant role in the professional growth of educators. Aim of the study was to explore the attitudes of the primary school teachers towards workshops, to make them aware about the importance workshops for professional development and to find out teachers skills of assessing the educational activities. A sample of 66 teachers of grade 5th was selected as respondents for the study. Observation and informal interview was conducted for data collection. Chi-Square was used for analysis of the observation sheet and for interviews, themes and patterns were developed. The study revealed that more than half of trainees have very low knowledge of assessment practices and some of them were even not interested in the workshop. The local office also showed little interest in the workshop. In the light of findings, merit based selection, proper planning for conduction of workshops, follow-up activities, local departmental interest and provision of suitable facilities i.e. man and material were recommended